Consequences of son preference in a low-fertility society : imbalance of the sex ratio at birth in Korea - Cho, Nam-Hoon; Park, Chai Bin
tbls., gráfs.
pp. 59-84
Keywords: Fecundidad; Masculinidad; Republica Popular Democratica de Corea